Lipopolysaccharide Signaling in the Carotid Chemoreceptor Pathway of Rats with Sepsis Syndrome - Maisey-Munoz, K; Acuna-Castillo, C (2011)
In addition to their role in cardiorespiratory regulation, carotid body (CB) chemoreceptors serve as sensors for inflammatory status and as a protective factor during sepsis. However, lipopolysaccharide-induced sepsis (LPS) reduces CB responsiveness to excitatory or depressant stimuli. We tested whether LPS exerts a direct effect on the carotid chemoreceptor pathway, the CB and its sensory ganglion. We determined that the rat CB and nodose-petrosal-jugular ganglion complex (NPJgc) express TLR4, TNF-? and its receptors (TNF-R1 and TNF-R2). LPS administration (15. mg/kg intraperitoneally) evoked MyD88-mechanism pathway activation in CB and NPJgc, with NF-?B p65, p38 MAPK, and ERK activation. Consistently, LPS increased TNF-? and TNF-R2. Double-labeling studies showed that the aforementioned pathway occurs in TH-containing glomus cells and NPJgc neurons, components of the chemosensitive neural pathway. Thus, our results suggest that LPS acting directly through TLR4/MyD88-mechanism pathways increases TNF-? and TNF-R2 expression in the carotid chemoreceptor pathway. These results show a novel afferent pathway to the central nervous system during endotoxemia, and could be relevant in understanding sepsis pathophysiology and therapy. © 2010 Elsevier B.V.